1996
DOI: 10.1111/j.1949-8594.1996.tb15862.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Parental Influence and Student Achievement in Seventh Grade Mathematics

Abstract: Parental influence has been identified as an important factor affecting student achievement, but the variables addressed by various parent‐school partnership programs vary, and lack literature support. This deficiency was ameliorated in this study through an analysis of a national data base from the Longitudinal Study of American Youth (LSAY). AH parental variables investigated in LSAY were considered in this study, and significant variables of students' achievement in seventh grade mathematics were selected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Shaver and Walls's (1998) study on eighth graders' mathematics and reading achievement, concluded that parental involvement, regardless of the child's gender or SES, was a positive influence on academic success. Wang et al (1996) show that parental education and encouragement are strongly related to seventh grade students' performance in mathematics. They obtained significant predictors of mathematics achievement using backwards elimination.…”
Section: Parental Influencementioning
confidence: 94%
See 2 more Smart Citations
“…Shaver and Walls's (1998) study on eighth graders' mathematics and reading achievement, concluded that parental involvement, regardless of the child's gender or SES, was a positive influence on academic success. Wang et al (1996) show that parental education and encouragement are strongly related to seventh grade students' performance in mathematics. They obtained significant predictors of mathematics achievement using backwards elimination.…”
Section: Parental Influencementioning
confidence: 94%
“…Many US studies have shown that, irrespective of a child's background, parental involvement has a positive impact on academic achievement (Wang et al 1996, Epstein et al 1997, Shaver and Wallis 1998, Dryfoos 2000, Starkey and Klein 2000. In a 4-month intervention experimental study using maths kits for home use, Starkey and Klein (2000) found that children in the experimental group whose mothers were taught how to use these kits developed greater maths knowledge and skills than those in the control group.…”
Section: Parental Influencementioning
confidence: 99%
See 1 more Smart Citation
“…The types of parental involvement studied can be generally categorised into two: direct assistance and indirect assistance (Cai et al, 1997). Direct assistance, such as helping children with mathematics difficulties and helping children with mathematics subject choice, was found to have a less important impact on students' mathematics performance (Cai et al, 1997;Wang et al, 1996). Indirect assistance, such as parental encouragement, parental expectation, and parents' attitudes towards mathematics, were frequently identified as having a significant impact on students' attitudes towards mathematics, students' participation in advanced level mathematics and students' achievement in mathematics (Ma, 2001;Poffensberg and Norton, 1959;Wang et al, 1996).…”
Section: On Mathematics Learningmentioning
confidence: 96%
“…Moreover, parents' social status and students' perception of family learning environments were found to be related to students' achievement. In addition, Wang, Wildman, and Calhoun (1996) (1996) parental involvement in terms of discussion of schooling with children at home was found to be significantly related to academic achievement. Therefore, findings in the literature in general indicated that parental influences not only related to students' motivation but also their achievement.…”
mentioning
confidence: 92%